Sosialisasi Pengolahan Pupuk Organik Padat (POP) dan Cair (POC) Berbasis Kotoran Kambing dalam Mengatasi Mahalnya Pupuk Kimia di Desa Girimulya Kecamatan Pacet Kabupaten Bandung - Setiawan, Asep Yanyan; Supriatna, Upi; Rasmilah, Ikeu; Nurwulan, Rinayanti Laela; Sudrajat, Ajat; Yusdian, Yudi (Universitas Pahlawan Tuanku Tambusai, 2025)
The problem faced by farmers is the price of fertilizer that continues to rise, especially if there is no subsidy that can ease farming capital. One solution that can be attempted in the problem of agricultural fertilizers is to reduce dependence on chemical fertilizers and switch to the use of organic fertilizers that are more environmentally friendly and easier to obtain. For agricultural areas such as Girimulya Village, Pacet District, Bandung Regency, where most of the farmers raise livestock, they can utilize livestock waste to be used as organic fertilizer, most of which still have few people who process animal waste into organic fertilizer. This Community Service tries to educate the people of Girimulya Village in utilizing animal waste as organic fertilizer, both solid and liquid types. The implementation of team which has been carried out through several stages, including initial surveys to the location, planning, testing of Solid Organic Fertilizer and Liquid Organic Fertilizer and applying it to plants, and the final stage is educating the community through posters.